(untitled) (Asian Journal of Medical and Biological Research, 2016)
The experiment was conducted to measure the feasibility of partial replacement of skim milk with different levels of coconut milk in the manufacture of dahi. Skimmed milk was replaced by 0, 5, 10, 15 and 20% of coconut milk to produce Dahi designated as A, B, C, D and E. All the samples were analyzed for organoleptic, chemical and microbiological qualities. Replacement of skim milk up to 10% with coconut milk increased total organoleptic score but score decreased when level of coconut milk was 15% and 20%. Dahi manufactured by incorporating 5% coconut milk gave superior results for body and consistency and also for colour and texture. In all levels of replacement increased fat, carbohydrates, ash and total solids were obtained, while protein and pH content were significantly decreased in Dahi samples. Total bacterial count was higher in the dahi manufactured by replacement of coconut milk than control. It could be concluded that 5 and 10% replacement of skim milk with coconut milk for the manufacturing of Dahi was acceptable and reduced the production cost and they were better in compare to others, according to organoleptic, chemical and microbiological analysis. The work showed the potential of coconut as an alternative source of skim milk in dahi manufacturing with improved nutritional value and consumer acceptability. Asian J. Med. Biol. Res. June 2016, 2(2): 247-252